Harinas de grillo doméstico Acheta domesticus, Mosca soldado negra Hermetia illucens, Gusano de la harina Tenebrio molitor como alternativas en la alimentación de bovino. - Monserrate Bastidas, Luigy Jareth (2024)
The present research focuses on the study of three types of flours that come from the following insects, the house cricket, the black soldier fly and the mealworm, with the aim of determining their potential as an alternative in cattle feed, the latter a problem that is currently reflected in the deforestation of large areas of forests. for the cultivation of grass, a traditional food in the livestock industry. Due to the relevance of the research, highly relevant and concrete content was integrated that provides the most information based on important aspects such as: the production system, physical-nutritional composition, microbiological, and its nutritional contribution in relation to the nutritional requirements of cattle. This worldwide trend makes insect meals become a point of interest for the generation of food products aimed at feeding cattle, where each meal has great nutritional qualities that would contribute to the development of cattle in different stages of growth, it is more an example of that is the meal worm meal that among its composition is calcium and calcium. Phosphorus, black soldier fly meal, has a significant protein content and domestic cricket flour has a variety of fatty acids.